Application of Google Classroom Media to Improve Social Studies Learning Outcomes The Environmental Theme of Our Friends in Class V of Elementary School - Thesalonika, Emelda; Simaremare, Juni Agus (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine the use of the Google Classroom application on social studies learning outcomes theme 8 Neighborhoods of Our Friends for class V SDN 091329 Bahpasunsang. This research is a Classroom Action Research (CAR) which consists of 2 cycles in which each cycle consists of 4 stages, namely planning, action, observation, and reflection. The data collection technique used is observation and test of learning outcomes. The results showed that in the pre-test of 33 students there were 33 students (100%) who did not reach the level of mastery learning with a class average of 22.2, then in the first cycle, 16 people (48.5%) students who achieved the level of complete learning with an average value of 55.6 while students who did not complete as many as 17 people (51.5%). In the second cycle as many as 32 people (94%) students who reached the level of mastery learning with an average value of 85.8 and 2 people (6%) students who did not complete. Thus, it can be concluded that Google Classroom-Based Blended Learning can improve student learning outcomes in social studies lessons with the theme Our Friendship Environment in Grade V Elementary School. As a follow-up, it is suggested for teachers to be able to design and use Google Classroom-Based Blended Learning in improving students' social studies learning outcomes